(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Bullying and stress put a great deal of strain on workplace wellness. Although the relationship between quality management and health is starting to become clear, no studies have been done on the correlation between workplace bullying and stress. The goal of the article is to investigate relationships among quality management principles, workplace wellness, and stress levels. A sample of Swedish secondary school teachers received a questionnaire that was developed using theory and prior research. The questionnaire contained previously created components for workplace wellness and quality management values. There were other constructions for stress, demand, control, and bullying. Both cluster analysis and correlation studies were performed. The results support the relationship between quality management and workplace wellness that was shown in earlier studies. The findings also suggest that quality management can give employees a greater sense of control over their working environment, reducing some of the negative consequences of workplace stress. The findings also indicate a connection between quality management and bullying at work. Furthermore, it was discovered that demand was unrelated to workplace health, but control was. There were found to be four groups of employees, each with a unique quality management, stress, and health profile.